Determinants of Breakfast Habits for Fatukoa Elementary School Students in Kupang City During the Covid-19 Pandemic - Susan Gita Permata Kalla; Marselinus Laga Nur; Daniela Boeky (Lontar : Journal of Community Health, 2022)
Breakfast is an activity of eating and drinking which is done in the morning before doing daily activities. A good breakfast consists of food sources of energy, building blocks, and sources of regulators. The benefit of breakfast is to increase concentration because the food consumed can increase blood glucose levels in blood circulation in the brain so that it can concentrate properly. The purpose of this study was to determine the determinants of breakfast habits of SD Inpres Fatukoa students, Kupang City. Analytic research with a cross-sectional design is the method used. All students in grades 4, 5, and 6 at SD Inpres Fatukoa, Maulafa District, Kupang City, with a total of 203 participants, were included in the study. The research sample amounted to 134 samples with a simple random sampling technique. The results showed that there was a significant relationship between gender where p.value = 0.000 <α (0.05), knowledge p.value = 0.000 <α (0.05) and parental rules p.value = 0.001 <α (0.05) with the habit of having breakfast in the students of SD Inpres Fatukoa, Kupang City. It is expected for parents to always prepare breakfast for their children with a nutritious and balanced nutritional breakfast for their children before leaving for school so that children can concentrate on studying at school and for the education office to provide input to be able to develop programs for health and nutrition education materials in the school curriculum. Keywords: breakfast habits, gender, knowledge, and parental rules